KEMAMPUAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 2 BATANG KAPAS KABUPATEN PESISIR SELATAN DENGAN MENGGUNAKAN TEKS WAWANCARA - Nurpida, Nurpida; Chan, Wirsal; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2014)
This research is a quantitative study, by using descriptive methods. The population is for grade eighth students of SMP Negeri 2 Batang Kapas Kabupaten Pesisir Selatan. This study is a test instrument performance. The results of this study indicate that the ability to write news forÂ grade eighth students of SMP Negeri 2 Batang Kapas kabupaten Pesisir Selatan by using a text interview is quite good (G) with an average of 80,95%mastery. The ability to write news for grade eighth students of SMP Negeri 2 Batang Kapas kabupaten Pesisir selatan by using a text interview seen from (1) headline indicators pertained More than enough with mastery 72,22%, (2) Indicators of what pertained More than enoughwith71,11%student mastery average,(3) indicators of whom are classified as good (G)with an average of 80,00%students mastery,(4) indicator when classified as good (G) with an student mastery average of 81,11%, (5) indicators where / which is quite very good (VG) with an average of 88,88% student mastery, (6) indicatorwhy quite good (G) with an average of 85,55% student mastery, and (7) indicators ofÂ how quite very good (VG) with an average of 87,77% student mastery.